2001
DOI: 10.1523/jneurosci.21-16-06308.2001
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 Receptors Reduce Release from Excitatory But Not Inhibitory Synaptic Inputs onto Lateral Horn Neurons

Abstract: Although adenosine is an important neuromodulator in the CNS, its role in modulating sympathetic outflow at the level of the spinal cord has not been studied. Because very little is known about adenosine A1 receptors (A1Rs) in the spinal cord, we determined their location and role with particular reference to the control of sympathetic preganglionic activity and interneuronal activity in the rat. High levels of immunoreactivity for A1Rs were observed throughout the spinal cord. Immunostaining was dense in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 39 publications
8
34
0
Order By: Relevance
“…Adenosine A1 and A2 A receptors are located on excitatory and inhibitory terminals, respectively synapsing onto the same neurons in the IML As previously reported, A1Rs are located exclusively on excitatory, not inhibitory, terminals, which synapse onto SPNs and interneurons in the IML (Deuchars et al, 2001b). In this study, we have shown that A2 A Rs are functionally located exclusively on inhibitory terminals, which also synapse onto SPNs and interneurons.…”
Section: The Effects Of Cgs 21680 On Ipsp Amplitude Are Attributable supporting
confidence: 80%
See 4 more Smart Citations
“…Adenosine A1 and A2 A receptors are located on excitatory and inhibitory terminals, respectively synapsing onto the same neurons in the IML As previously reported, A1Rs are located exclusively on excitatory, not inhibitory, terminals, which synapse onto SPNs and interneurons in the IML (Deuchars et al, 2001b). In this study, we have shown that A2 A Rs are functionally located exclusively on inhibitory terminals, which also synapse onto SPNs and interneurons.…”
Section: The Effects Of Cgs 21680 On Ipsp Amplitude Are Attributable supporting
confidence: 80%
“…Hence, for some experiments, CGS 21680 was applied in the presence of the A1R antagonists 8-cyclopentyl-1,3-dipropylxanthine (DPCPX) (50 nM; n ϭ 7) or CPT (10 M; n ϭ 25). Administration of DPCPX (50 nM) or CPT (10 M) alone had no effect on the evoked EPSP as expected (results not shown; Deuchars et al, 2001b). No significant effect was observed on the evoked EPSP in interneurons after the application of CGS 21680 alone (25 nM, 6.5 Ϯ 0.4 to 6.5 Ϯ 0.4; n ϭ 5 ; Fig.…”
Section: The A2 a R Agonist Cgs 21680 Has No Effect On Epsps Elicitedsupporting
confidence: 78%
See 3 more Smart Citations